Building cultural intelligence in an age of incivility : growing in CQ through holistic discipleship - Hawkins, Vanessa K. (2022)
1 online resource (xi, 106 leaves); Abstract; Thesis (D. Min.)--Covenant Theological Seminary, 2022; Includes bibliographical references (leaves 104-106)